ANALISIS PENGARUH IKLIM KERJA DAN PENGEMBANGAN KARIR TERHADAP KOMITMEN KARIR: KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi kasus pada karyawan PT Pertamina (Persero) Pemasaran Wilayah Jawa Tengah dan DIY) - Adi Siswanto, Eko; Yuniawan, Ahyar (Faculty of Economics and Business Diponegoro University, 2012)
The purpose of this study was determinate the influence between work climate on job satisfaction, influence between career development on job satisfaction, and the influences between job satisfaction on career commitment. In this study The research data was collected from 60 employees in 11 job functions that are not derived from the managerial class and still be productive on a vulnerable age. Questions is given by using a questionnaire distributed through random sampling technique which respondents were randomly selected using random numbers. After the questionnaire collected, data test technique used within a research by using the index value, validity index by factor analysis, regression, and Sobel Test to tested mediating effect by the program of PASW SPSS 18. The result indicated that the work climate and career development has positive and significant effect to job satisfaction and job satisfaction has positive and significant influence to career commitment. With the influence of 53,61% and 46,39% while the other can be influenced by other variables.